Advanced Nanotechnologies for Detection and Defence against CBRN Agents (NATO Science for Peace and Security Series B: Physics and Biophysics,, 2018)
This volume gives a broad overview of advanced technologies for detection and defence against chemical, biological, radiological and nuclear (CBRN) agents. It provides chapters addressing the preparation and characterization of different nanoscale materials (metals, oxides, glasses, polymers, carbon-based, etc.) and their applications in fields related to security and safety. In addition, it presents an interdisciplinary approach as the contributors come from different areas of research, such as physics, chemistry, engineering, materials science and biology. A major feature of the book is the combination of longer chapters introducing the basic knowledge on a certain topic, and shorter contributions highlighting specific applications in different security areas.